Analysis Of Consumer Purchase Satisfaction Of Otc Or Non-Precipation Medicine On The Influence Of Price Competition, Service Performance, And Word Of Mouth (Case Study On Consumers Of Otc Non-Precipation Medicine In Pharmacies In Pontianak City) - Maisirata, Pasifikus (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to see whether there is an influence of competitive prices, service performance, and word of mouth on consumer satisfaction who buy non-prescription over-the-counter drugs in pharmacies in Pontianak city. The form of research used is causal relationship research, data collection techniques using interviews, questionnaires, and observations. The sampling technique used accidental sampling with a total of 115 respondents. Data analysis techniques using quantitative analysis, using a rating scale and to process data in this study using the SPSS 26 program. Based on the test results, it can be concluded that the results of simultaneous testing (F test) indicate that competitive prices and service performance do not affect consumer satisfaction while word of mouth has an influence on consumer satisfaction who buy non-prescription over-the-counter drugs in Pontianak city. The results of partial testing (T test) indicate that competitive prices and service performance do not affect consumer satisfaction, while word of mouth has an influence on consumer satisfaction of non-prescription over-the-counter drugs in pharmacies in Pontianak city.